The impact of autophagy on arbovirus infection of mosquito cells - Brackney, Doug E. (PLoS Negl Trop Dis, 2020)
Macroautophagy is an evolutionarily conserved cellular process critical for maintaining cellular homeostasis. It can additionally function as an innate immune response to viral infection as has been demonstrated for a number of arthropod-borne (arbo-) viruses. Arboviruses are maintained in a transmission cycle between vertebrate hosts and invertebrate vectors yet the majority of studies assessing autophagy-arbovirus interactions have been limited to the mammalian host. Therefore we evaluated the role of autophagy during arbovirus infection of the invertebrate vector using the tractable Aag2 Aedes aegypti mosquito cell culture system. Our data demonstrates that autophagy is significantly induced in mosquito cells upon infection with two divergent arboviruses: dengue virus-2 (DENV-2; Flaviviridae, Flavivirus) and chikungunya virus (CHIKV; Togaviridae, Alphavirus). While assessing the role of autophagy during arbovirus infection, we observed a somewhat paradoxical outcome. Both induction and suppression of autophagy via torin-1 and spautin-1, respectively, resulted in increased viral titers for both viruses, yet suppression of autophagy-related genes had no effect. Interestingly, chemical modulators of autophagy had either no effect or opposite effects in another widely used mosquito cell line, C6/36 Aedes albopictus cells. Together, our data reveals a limited role for autophagy during arbovirus infection of mosquito cells. Further, our findings suggest that commonly used chemical modulators of autophagy alter mosquito cells in such a way as to promote viral replication; however, it is unclear if this occurs directly through autophagic manipulation or other means.